Strategi Perencanaan Jaringan Pipa Distribusi Air Bersih di Desa Pasiraman Kecamatan Wonotirto Kabupaten Blitar - Rohman, Haniv Avivu; Hidayati, Nur; Farida, Eka (Universitas Nahdlatul Ulama Blitar, 2025)
Pasiraman Village, located in Blitar Regency, is a highland area characterized by rocky mountains and geologically classified as limestone. This condition results in less fertile, dry, and barren soil structure in the region. Given these conditions, immediate action is needed to provide clean water, with the primary goal of meeting the community's clean water needs in terms of quantity, quality, and continuity. In Pasiraman Village, the Beji spring, located at an elevation of 250 meters above sea level in Krajan Hamlet, serves as the water source, with a flow rate of 58 liters per second. This study plans the clean water distribution pipeline network using the Epanet 2.0 software. The outputs generated by Epanet 2.0 include the flow rate within the pipes and the water pressure at each point/node/junction, which are used for analyzing the operation of installations, pumps, and reservoirs. These outputs can also be used as simulations for determining the location of sources for development direction. The projected population of Pasiraman Village in 2031 is 10,873 people, with a planned water demand flow rate of 29.1796 liters per second. The dimensions of the clean water distribution pipes in Pasiraman Village will use PVC pipes of 6”, 5”, and 2.5”, and the surface reservoir dimensions will be 9 x 6 x 4.5 meters, made of reinforced concrete.